Analisis Kemampuan Computational Thinking Mahasiswa Dalam Menyelesaikan Masalah Matematika - yuntawati, yuntawati; Sanapiah, Sanapiah; Aziz, Lalu Abdul (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
Mathematics learning is always related to problems. Computational Thinking is a thought process that is needed in formulating a problem and its solution. Prospective mathematics teachers have the responsibility to equip themselves with various abilities including Computational Thinking which will become their provisions when they become teachers. As a first step to prepare strategies that can be used in improving and developing students 'computational thinking skills, it is necessary to know and first how the students' computational thinking skills. This type of research is descriptive qualitative. The research respondents were 10 students of UNDIKMA mathematics education. Respondent categories are students who have taken Graph courses. The technique of determining respondents is a random sampling method. The research data interview techniques were tests and interviews. The instruments used are two questions to solve math problems. The results shown in solving the first and second questions show that respondents are able to solve problems with the Computational Thinking component. begins with decomposition, abstraction, and algorithms. While the generalization component is not visible in the problem solving process, although there were some respondents who answered incorrectly. This is because the respondents do not understand the questions. Questions are only read once or twice so the information in the questions has not been properly implemented. Even the respondents only saw the simplest paths and ignored the winding paths in solving the second problem.